Comparative efficiency of liquid and granular urea fertilizers on nitrogen dynamics, growth performance and yield of grain corn (Zea mays L.) - Ahmmed, Md. Motasim (2022)
Urea is the most popular, user-friendly nitrogen (N) fertilizer having significant contributions to worldwide crop production. Urea mineralization regulates the N dynamics and N content of the soil. A huge amount of N from granular urea (GU) might be lost through nitrate (NO3) leaching, ammonia (NH3) volatilization, and denitrification resulting in low Nitrogen Use Efficiency (NUE). It was hypothesized that the N losses could be minimized if urea hydrolysis is fast so that the ammonium cations (NH4+) are more uniformly distributed throughout the soil profile. There is no single method which can effectively restrict NO3 leaching and NH3 and N2O gaseous losses from applied urea except by reducing the application rate. The general objective of the study was to compare the effectiveness of GU and liquid urea (LU) with its split application as N sources for grain corn (Zea mays L.) grown cultivation. The first experiment was an incubation study conducted in laboratory settings to compare the N dynamics and losses in two soil series incubated with either LU or GU at 0, 300, 400 or 500 mg/kg of soil arranged in a Completely Randomized Design (CRD) layout with four replicates. The NH4+ and NO3- concentrations in the soils were measured for four weeks, while the N leaching loss was measured for ten pore volumes. Ammonia volatilization, N2O emission, and soil N content were measured throughout the 30 days incubation period. The results showed that higher NH4+ and NO3- concentrations at the same application rate were detected in the LU applied soils. The leaching loss of N was higher in GU treated soils than that of LU, and it increased with an increase in urea application rate. The N2O emission and NH3 volatilization loss were also higher in GU than in the LU treated soils. The total N content that remained in the LU treated soils after incubation was higher than that of GU. The second experiment was conducted in a glasshouse to evaluate the effects of LU application frequency on the growth, yield and NUE of grain corn. The treatments consisted of a control (no urea application), granular urea applied as two equal splits (GU2S), liquid urea applied as two equal splits (LU2S), liquid urea applied as three equal splits (LU3S) and liquid urea applied as four equal splits (LU4S) arranged in a Randomized Completely Block Design (RCBD) with four replicates. Results indicated that among all the treatments, the grain corn receiving LU3S had the highest stem diameter (2.03 cm), cob weight (248.25 g), 100-grain weight (29.08 g), N uptake (133.96 kg/ha) and NUE (72.84%). The highest grain yield was recorded in the LU3S (6766.77 kg/ha) treatment, which was 37% higher than the GU2S (4942.90 kg/ha) treatment. The third experiment was also a glass house study conducted to determine the effects of application method and rates of LU on grain corn production. The experiment was conducted as an RCBD with four replicates. The fertilizer treatments were U0 = Control, GU100 (GU applied 100% in two splits at 10th and 28th DAS), LU100 (LU applied 100% a in two splits at 10th and 28th DAS), LU50 (LU applied 50% in two splits at 10th and 28th DAS) and LU33 (LU applied 33% in two splits at10th and 28th DAS). The higher ear length (22.88 cm), 100-grain weight (22.50 g), grain weight (102.17 g/plant), husk weights (25.26 g/plant) and grain yield (6249.03 kg/ha) were observed in the LU100 treatment, but the values were statistically similar to GU100 and LU50 treatments. The N uptake (%) by the grain was also highest in LU100 (1.489 g/plant), while the value in LU50 (1.272 g/plant) was higher than the GU100 (1.159 g/plant), and the highest N uptake was recorded in LU100 (102.83 kg/ha). The NUE was highest in LU50 (66.92%), followed by LU100 (51.47 %) treatment. The final experiment was a two-cycle field study conducted to evaluate the N uptake and NUE of different LU application splits, along with their effects on the growth, development and yield of grain corn in the field and the experiments were conducted as a RCBD with four replicates. The treatments were T0 (No urea) as a control, T1 (100% GU in two splits at 10th and 28th DAS), T2 (100% LU in two splits at 10th and 28th DAS), T3 (100% LU in three splits 10, 40 and 65 DAS), T4 (50% LU in two splits at 10th and 28th DAS) and T5 (50% LU in three splits 10, 40 and 65 DAS). Results revealed that the ear length, cob diameter, cob weight, number of seeds per kernel row, grain weight /plant, 100-grain weight and grain yield were recorded highest in T3 for both seasons. However, the 100-grain weight of T3 (50.51 g) was not statistically different from T2 (49.02 g). The highest grain yield was also recorded in T3 (11019.23 kg/ha), followed by the T2 (9902.51 kg/ha) treatment. The grain yield data between the two seasons were similar when compared within similar treatment. The N uptake (161.92 kg/ha) was highest in T3, but there was no statistical difference in NUE between T3 (77.42 %) and T5 (75.42 %). Overall, the study suggests that the LU was a better N fertilizer source than GU because N mineralization and N availability were more rapid while N leaching and gaseous losses were significantly lower. The results also suggest that T3 (100% LU applied in 3 splits) was the most efficient treatment for optimizing the growth and yield of grain corn.